Lebensform Universität Ehrengabe für Andreas Ranft - Krüger, Klaus 1960-; Meinhardt, Matthias 1969-; Ruprecht, Michael 1978-; Selzer, Stephan 1968- (De Gruyter, 2023)
This volume brings together ten essays in honor of Andreas Ranft. They examine important facets of the university as a way of life, viewing it as a place that generates meaning and fosters community, making it much more than a place of education or one station in a professional career. The texts cover a period spanning the medieval beginnings of the university to the reform debates that took place in the German postwar period